Late Outcomes of Carotid Artery Stenting for Radiation Therapy-Induced Carotid Stenosis. (December 2022) - Nasr, Bahaa; Crespy, Valentin; Penasse, Edouard; Gaudry, Marine; Rosset, Eugenio; Feugier, Patrick; Gouëffic, Yann; Maurel, Blandine; Hostalrich, Aurélien; Alric, Pierre; Sadaghianloo, Nirvana; Settembre, Nicla; et al.
Purpose: Carotid artery stenting (CAS) appears as a promising alternative treatment to carotid endarterectomy for radiation therapy (RT)-induced carotid stenosis. However, this is based on a poor level of evidence studies (small sample size, primarily single institution reports, few long-term data). The purpose of this study was to report the long-term outcomes of a multicentric series of CAS for RT-induced stenosis. Methods: All CAS for RT-induced stenosis performed in 11 French academic institutions from 2005 to 2017 were collected in this retrospective study. Patient demographics, clinical risk factors, elapsed time from RT, clinical presentation and imaging parameters of carotid stenosis were preoperatively gathered. Long-term outcomes were determined by clinical follow-up and duplex ultrasound. The primary endpoint was the occurrence of cerebrovascular events during follow-up. Secondary endpoints included perioperative morbidity and mortality rate, long-term mortality rate, primary patency, and target lesion revascularization. Results: One hundred and twenty-one CAS procedures were performed in 112 patients. The mean interval between irradiation and CAS was 15 ± 12 years. In 31.4% of cases, the lesion was symptomatic. Mean follow-up was 42.5 ± 32.6 months (range 1–141 months). The mortality rate at 5 years was 23%. The neurologic event-free survival and the in-stent restenosis rates at 5 years were 87.8% and 38.9%, respectively. Diabetes mellitus (p=0.02) and single postoperative antiplatelet therapy (p=0.001) were found to be significant predictors of in-stent restenosis. Freedom from target lesion revascularization was 91.9% at 5 years. Conclusion: This study showed that CAS is an effective option for RT-induced stenosis in patients not favorable to carotid endarterectomy. The CAS was associated with a low rate of neurological events and reinterventions at long-term follow-up.